2020
DOI: 10.1111/jopr.13249
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness of Milled Lithium Disilicate With and Without Reinforcement After Finishing and Polishing: An In Vitro Study

Abstract: Purpose To determine the efficacy of various finishing and polishing techniques on the surface roughness of two computer‐aided design/computer‐aided manufacturing (CAD/CAM) materials, lithium disilicate (IPS e.max), lithium disilicate reinforced with lithium aluminosilicate (Straumann® n!ce™), and a stackable low‐fusing nanofluorapatite glass ceramic (Ceram). Materials and Methods Flat specimens (n = 12) per treatment group were fabricated 2 mm thick, 15 mm in length, and 12mm in width. Samples were either gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…They also found that polishing could create residual compressive strength that would further harden the surface of the ceramic restoration. Although various polishing systems for ceramic restoration have been widely studied,[ 2 3 4 5 6 7 8 9 10 11 12 ] most studies focused on the roughness of ceramics polished by their specific ceramic polishing systems compared with other methods such as Sof-Lex,[ 2 ] Identoflex[ 3 4 ] or diamond polishing paste. [ 3 4 5 6 ] Some studies compared the roughness of ceramics between feldspathic and zirconia polishing sets[ 7 8 9 ] or the effectiveness of universal ceramic polishing sets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that polishing could create residual compressive strength that would further harden the surface of the ceramic restoration. Although various polishing systems for ceramic restoration have been widely studied,[ 2 3 4 5 6 7 8 9 10 11 12 ] most studies focused on the roughness of ceramics polished by their specific ceramic polishing systems compared with other methods such as Sof-Lex,[ 2 ] Identoflex[ 3 4 ] or diamond polishing paste. [ 3 4 5 6 ] Some studies compared the roughness of ceramics between feldspathic and zirconia polishing sets[ 7 8 9 ] or the effectiveness of universal ceramic polishing sets.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 5 6 ] Some studies compared the roughness of ceramics between feldspathic and zirconia polishing sets[ 7 8 9 ] or the effectiveness of universal ceramic polishing sets. [ 10 11 12 ] There has been limited data regarding the effectiveness of the lithium disilicate polishing set. Therefore, this study aimed to examine the surface roughness of three types of dental ceramics after polishing with three extraoral ceramic polishing systems: feldspathic porcelain, lithium disilicate, and zirconia polishing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Translucency is an important optical property for dental ceramics needed to mimic natural dentition. Translucency has been described as the amount of light transmitted or diffused from the substrate 11,12 . Even though pigments can be applied to dental ceramics to obtain a high translucency look, this stain can be lost within a few months after exposure to everyday products such as toothpaste and beverages such as tea and coffee 13,14 .…”
mentioning
confidence: 99%
“…However, precautions should be considered during polishing as thinning of ceramic restorations might occur which increases the risk of ceramic fracture 12 . However, other studies have found no difference in surface roughness of dental ceramics after using either polishing pastes/kits or glazing techniques 17,18 . This might be due to the difference in composition of dental ceramics and particle size studied.…”
mentioning
confidence: 99%
“…12 However, other studies have found no difference in surface roughness of dental ceramics after using either polishing pastes/kits or glazing techniques. 17,18 This might be due to the difference in composition of dental ceramics and particle size studied.…”
mentioning
confidence: 99%